KERAGAMAN LUMUT DAUN DI HUTAN BEKAS TERBAKAR BUKIT BANGKIRAI, KALIMANTAN TIMUR=MOSS DIVERSITY IN THE FOREST FIRE FROM BUKIT BANGKIRAI, EAST KALIMANTAN - Windadri, Florentina Indah; Haerida, Ida; Yamaguchi, Tomio; Shimizu, Hideyuki (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Bukit Bangkirai is a public recreation forest in East Kalimantan. During the long dryÃ‚Â season in 1982-1983 and 1997-1998 some parts of the forest have burnt out, only smallÃ‚Â part war escaped. Bryophytes are small plant and usually abundantly grows on the forest.The Bryodiversity research in the Bukit Bangkirai has been done in the 2000 to 2003.Total sample of bryophyte collections about 3000 numbers since seven period collections and the result of identification were found 92 species including 27 genera and 9 families.The dominant mosses found are Achantorrhynchium papilatum, Arthrocormus schimperi,Leucobryum sanctum, Octoblepharum albidum, Pyrrhobryum spiniforme, Syrrhopodonalbovaginatus and Syrrhopodon spiculosus. Only four species found in control plot.They are Ctenidium malacobolum, Fissidens zippleianus, Groutiella tomentosa andÃ‚Â Taxithellium lindbergii. Acroporium diminutum, Leucobryum juniperinoides, CalymperesÃ‚Â aeruginosum, Fissidens robinsonii and Syrrhopodon semilimber were only found in theÃ‚Â light damage plot and Fissidens wichurae, Isopterygium textori, Leucobryum bowringii,Syrrhopodon confertus were only found in the heavy damage plot. The mosses usuallygrows on the soil and rotten logs in damp site.Key words: Bangkirai forest recreation, east Kalimantan, mosses, burn areas,diversity.